IKLIM ORGANISASI KELURAHAN DALAM PERSPEKTIF EKOLOGI - Destiani Putri Utami; Dwi Melliani; Fermim Niman Maolana; Fitriana Marliyanti; Asep Hidayat (Sekolah Tinggi Pariwisata Mataram, 2021)
Cibangkong Village is one of the villages located in Batununggal District, Bandung City, West Java. In its operations, of course every organization is required to be able to implement and demonstrate a good organizational climate. Organizational climate has an important role in improving employee performance. This study aims to determine what the organizational climate is like in the Kelurahan Cibangkong Office, Batununggal Subdistrict, Bandung City as an evaluation material that will affect the formation of an organizational climate in an agency which impacts on job satisfaction, and ends on the performance of the organization / agency. The problem in this research is regarding the review of organizational climate health at the Cibangkong Village Office, Batununggal District, Bandung City. Data collection techniques in this study were observation, interviews and literature study / documentation. The technique of selecting informants using purposive sampling. The results showed that the organizational climate in the Kelurahan Cibangkong Office, Batununggal Subdistrict, Bandung City was quite good because the results showed that external environmental factors, organizational strategy, organizational arrangements, historical strength, and leadership, have continuously formed a system that supports each other. other.